Fabrication and Tribology Properties of PTFE-Coated Cemented Carbide Under Dry Friction Conditions - Shoujun Wang; Wenlong Song; Lei An; Zixiang Xia; Shengdong Zhang (Lubricants)
PTFE coatings were deposited on YT15 carbide substrates using spray technology. A series of examinations were conducted, including the use of surface and cross-section micrographs to analyze the structural integrity of the coatings. The surface roughness, the adhesion force between the PTFE coatings and the carbide substrate, and the micro-hardness of the coated carbide were also evaluated. Additionally, the friction and wear behaviors were assessed through dry sliding friction tests against WC/Co balls. The test results indicated that while the PTFE-coated carbide exhibited a rougher surface and reduced micro-hardness, it also demonstrated a significant reduction in surface friction and adhesive wear. These findings suggest that the PTFE coatings enhance the overall wear resistance of the carbides. The lower surface hardness and shear strength of the coatings influenced the friction performance, leading to specific wear failure mechanisms, such as abrasion wear, coating delamination, and flaking. Overall, the deposition of PTFE coatings on carbide substrates presents a promising strategy to enhance their friction and wear performance. This approach not only improves the durability of carbide materials but also offers potential applications in industries where reduced friction and wear are critical for performance.